Rivers - Chapman, Garry (Broomall, PA : Chelsea House, 2002)
Provides photographs and information about the extreme sports of whitewater kayaking, whitewater rafting, riverboarding, and canyoneering; and includes information about some of the athletes who participate in these daring activities.
"First published in 2001 by Macmillan Education Australia ... South Yarra, Australia"--T.p. verso.
Includes index.
6.7
3-6
Keywords: Kayaks -- Juvenile literature; Rafting (Sports) -- Juvenile literature; Canyoneering -- Juvenile literature; Extreme sports -- Juvenile literature; Kayaks and kayaking; Rafting (Sports); Canyoneering; Extreme sports; Kayaks; Rafting (Sports); Canoes and canoeing; Extreme sports